Synthesis and Characterization of Some Biologically Significant Thiazolidinones - Rama Rao, Nadendla; Ramu, B.; Gopinath, C. (Asian Journal of Chemistry, 2010)
Some new 2-(aryl or substituted aryl)-3-(3´-fluoro-4´-chloro phenyl) thiazolidinones were synthesized by cyclocondensation of anils with thioglycollic acid. The synthesized compounds were established by spectral analysis and evaluated for antimicrobial properties.